2012
DOI: 10.1038/nature11684
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the proton-gated urea channel from the gastric pathogen Helicobacter pylori

Abstract: Half the world's population is chronically infected with Helicobacter pylori1, causing gastritis, ulcers and increased incidence of gastric adenocarcinoma2. Its proton-gated inner-membrane urea channel, HpUreI, is essential for survival in the acidic environment of the stomach3. The channel is closed at neutral pH and opens at acidic pH to allow rapid urea access to cytoplasmic urease4. Urease produces NH3 and CO2 that neutralize entering protons and thus buffer the periplasm to pH ∼6.1 even in gastric juice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 36 publications
2
102
0
Order By: Relevance
“…The former cluster, closely related to that found in H. pylori, is induced by Ni 2ϩ and encodes two structural genes, a proton-gated urea channel (82), and the four standard maturation proteins. The latter cluster is inversely regulated by Ni 2ϩ and encodes only the two structural genes (83).…”
Section: Variations In Urease Activation Systemsmentioning
confidence: 99%
“…The former cluster, closely related to that found in H. pylori, is induced by Ni 2ϩ and encodes two structural genes, a proton-gated urea channel (82), and the four standard maturation proteins. The latter cluster is inversely regulated by Ni 2ϩ and encodes only the two structural genes (83).…”
Section: Variations In Urease Activation Systemsmentioning
confidence: 99%
“…[23][24][25][26] The central regions of such channels are narrow (accommodating several dehydrated urea molecules in single-file) and largely hydrophobic (but with a small portion of polar/charged groups), [23][24][25][26] the environments of which are somewhat similar to the model system herein (a narrow, hydrophobic SWNT with an external charge). The findings in this study might also shed light on the mechanism of biological urea channels, [23][24][25][26] such as the competitive binding between urea and water onto the polar/charged residues of the channel, and how polar/charged groups modulate urea's orientation/binding in the constricted selectivity filter. In particular, our findings suggest a potential "electrostatic gating" 8 mechanism (trapping water/urea molecules in the confined region by the charged residue) for urea channels, which complements the previously observed steric gating mechanism for the urea channel of Helicobacter pylori.…”
Section: Discussionmentioning
confidence: 94%
“…Urea is a typical organic molecule with high polarity (the most widely used value of urea's dipole moment is 4.56 D measured in dioxane 22 ). It plays an important role in the metabolism of nitrogen-containing compounds by animals, [23][24][25][26] and serves as an important raw material for the chemical industry and a common chemical denaturant of proteins. [27][28][29] Our previous molecular dynamics (MD) simulations have shown that when SWNTs are solvated in urea solutions, urea molecules can induce drying of SWNTs, 30 resulting in 1D urea wires with concerted dipole orientations and slower flipping than water wires.…”
Section: Introductionmentioning
confidence: 99%
“…Two crystal structures of the UTs, dvUT [8] and UT-B [9], and one crystal structure of the proton-gated urea channel from Helicobacter pylori , HpUreI, [10] have been solved so far. These three-dimensional atomic structures have provided invaluable tools for us to understand the functional characteristics of UTs.…”
Section: Introductionmentioning
confidence: 99%